Effectiveness of Baby Powder Locking Technique on Durability of Toraja Fantasy Makeup - Huwaida, Dindaswari Fathiya; Krisnawati, Maria (Journal of Creativity Student, 2026)
The ephemeral nature of water-based body painting presents significant technical challenges in tropical climates, particularly regarding durability against perspiration and friction during long duration performances. This study explores a material innovation using a baby powder locking technique to enhance pigment adhesion and achieve a specific matte aesthetic resembling "dry bone" (To Makula). The artwork, titled "The Eternal Beauty of Death from Tongkonan House," reinterprets the Toraja Aluk Todolo philosophy through fantasy makeup. Employing a mixed-method design, the research integrates Practice Art-Based Research (PABR) through three creation cycles exploration, experimentation, and realization and a descriptive quantitative approach for product feasibility testing. Experimental results demonstrate that the intermediate and layering locking techniques successfully prevented pigment oxidation and cracking. The makeup maintained visual integrity for approximately 12 hours (03:00 AM to 02:50 PM), withstanding intense stage lighting and outdoor parade conditions as evidenced during the Gelar Karya event. Expert validation involving three specialists yielded an average feasibility score of 93%, categorizing the product as "Very Feasible," with the Visual Aesthetics indicator achieving the highest score of 98%. The study concludes that this domestic material intervention offers a cost-effective, high-durability solution for professional fantasy makeup, successfully synthesizing traditional cultural narratives with avant-garde technical application.